Taxonomic revision of the type specimens of Ethiopian Nippostrongylinae (Nematoda) deposited at the Natural History Museum of London - Durette Desset, Marie Claude (2010)
We studied the original material of several species of Nippostrongylinae (Nematoda: Heligmonellidae) described by H. A. Baylis in muroid rodents from Nigeria: Heligmonina praomyos Baylis, 1928, Heligmonina oenomyos Baylis, 1928, Heligmonina cricetomyos  Baylis, 1928, Neoheligmonella affinis (Baylis, 1928), Neoheligmonella intermedia (Baylis, 1928), Neoheligmonella gracilis (Baylis, 1928),  Neoheligmonella impudica (Baylis, 1928), Neoheligmonella moennigi (Baylis, 1928), and Heligmonoides murina Baylis, 1928. The comparison of the material examined to the original descriptions, revealed the presence of at least seven other species mixed among the type and voucher material. For the nominal species of Baylis lectotypes and paralectotypes are designated. Due to the poor condition of the material, the other species found were only identifiable to generic level. Most of them were coparasitic with Baylis’ species. The following species associations were found: Heligmonina praomyos + Neoheligmonella moennigi, Heligmonina oenomyos + Neoheligmonella sp. 1, Heligmonina cricetomyos + Neoheligmonella moennigi, Heligmonina sp. 2 + Neoheligmonella sp. 4. Tables with the identification of the specimens studied are provided. New morphometrical data and illustrations on this material are also provided, particularly on the anterior part of the body and genital apparatus in the females. The occurrence of coparasitism as a frequent phenomenon among the Trichostrongylina is highlighted.